2019
DOI: 10.3389/fmars.2019.00572
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Genomic Characterization of a Pseudomonas aeruginosa Strain Isolated From the Southwestern Gulf of Mexico Reveals an Enhanced Adaptation for Long-Chain Alkane Degradation

Abstract: Indigenous bacterial populations play an important role in the restoration of crude oilpolluted marine environments. The identification and characterization of these bacteria are key in defining bioremediation strategies for the mitigation of possible future oil spills. In this work, we characterized Pseudomonas aeruginosa strain GOM1, which was isolated from the water column in the southwestern Gulf of Mexico. Phylogenetic analysis revealed that GOM1 strain was most closely related to P. aeruginosa WC55, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…The diversity of sequences suggests microorganisms have the intrinsic potential to degrade a wide range of hydrocarbon compounds, as might be the case in an oil spill event. alkB genes are associated with the degradation of C10-C28 alkanes ( Van Beilen and Funhoff, 2007 ; Nie et al, 2014 ; Muriel-Millán et al, 2019 ), and we detected the majority of these sequences in water samples. The high diversity of Rieske oxygenases in water samples and in the A04 and E03 sediments, indicates there is potential for degradation of diverse aromatic compounds such as benzoate, benzene, toluene, phthalate, naphthalene or biphenyl ( Duarte et al, 2014 ).…”
Section: Discussionmentioning
confidence: 82%
“…The diversity of sequences suggests microorganisms have the intrinsic potential to degrade a wide range of hydrocarbon compounds, as might be the case in an oil spill event. alkB genes are associated with the degradation of C10-C28 alkanes ( Van Beilen and Funhoff, 2007 ; Nie et al, 2014 ; Muriel-Millán et al, 2019 ), and we detected the majority of these sequences in water samples. The high diversity of Rieske oxygenases in water samples and in the A04 and E03 sediments, indicates there is potential for degradation of diverse aromatic compounds such as benzoate, benzene, toluene, phthalate, naphthalene or biphenyl ( Duarte et al, 2014 ).…”
Section: Discussionmentioning
confidence: 82%
“…Natural leaks of oil are widely distributed in the GoM (MacDonald et al, 2015), suggesting that it has a basal level of HDB that can grow to address large-scale oil spills. This hypothesis was validated during the oil spill of the DWH and in later studies, in which metagenomic analysis and isolated cultures showed significant enrichment of bacterial populations related to Oceanospirillum, Cycloclasticus, Colwellia, Pseudoalteromonas, Rhodobacterales, methylotrophs, Alcanivorax, Oleiphilus, Oleispira, Thalassolituus, Oceanospirillales, Marinobacter, Acinetobacter, Pseudomonas and Planomicrobium (Hazen et al, 2010;Kostka et al, 2011;Redmond and Valentine, 2012;Mason et al, 2012;Dubansky et al, 2013;Kimes et al, 2013;Mason et al, 2014;Kleindienst et al, 2015;Orcutt et al, 2017;García-Cruz et al, 2018;Muriel-Millán et al, 2019;Uribe-Flores et al, 2019;Cerqueda-García et al, 2020;Rodríguez-Salazar et al, 2020).…”
Section: Hydrocarbon-degrading Bacteriamentioning
confidence: 66%
“…Raggi et al (2020) determined the oxygen concentration in the Perdido Fold Belt zone (7.07 and 3.6 mg/L) and in the Campeche Knolls area (6.9 to 3.5 mg/L), for water column and sediments, respectively. Likewise, in these areas, similar alkB genes sequences related to the aerobic degradation of alkanes (Muriel-Millán et al, 2019) were found mainly in the water column, while in a in Campeche Knolls area sediment sample where anaerobic conditions prevail, shows a high diversity of bssA-like sequences, involved in anaerobic degradation of hydrocarbon (Acosta-González et al, 2013).…”
Section: Hydrocarbon-degrading Bacteriamentioning
confidence: 81%
See 1 more Smart Citation
“…Among the OTUs, the most abundant family of Pseudomonadaceae was OTU_001, which was identified as Pseudomonas aeruginosa. The P. aeruginosa was already known as a player in biodegradation of many substrates such as glycerol [33], diesel oil [34], water column-contaminated oil [35], polluted coastal area [36,37], PAH [38], and more.…”
Section: Discussionmentioning
confidence: 99%